(3GdebUO GdLdjd aj Yde GdNdjds - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s; (3GHf GdMGLH , LeGd GdOjf CHh YeQh GHf GdMGLH, LeGd GdOjf CHh YeQh GHf GdMGLH,J (B646 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Pi GdYQT GdeLjO Ydi EdjGSg ef dHGS aVdg MddkG s
(3YQhV GHf GdMGLH GdeSeGg HGdebUO GdLdjd ai Yde GdNdjds
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3fXes
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdYQhV hGdbhGais